APB UiTM Sarawak conducted two series of language workshop for Borneo Cultures Museum - Ibrahim, Sueb; Arabi, Arrominy; Ismailly, Norlida; Rijeng, Jacqueline Susan (Universiti Teknologi MARA, Sarawak, 2024)
The workshop focused mainly on developing effective communication skills among the staff, especially the frontliners, who are expected to be able to communicate effectively and professionally with the visitors. The three-day programme was designed to increase the participants’ language knowledge and enhance their non-verbal language skills which would allow them to be better communicators.